PREGNANCY DETECTION OF IRAQI SHE-CAMELS (Camelus dromedarius) USING VARIOUS TECHNIQUES - T. A. Abdulkareem (The Iraqi Journal of Agricultural science)
A study was conducted to investigate the most sensitive, early, and precise methods for detecting pregnancy in Iraqi She-camels using plasma progesterone levels, ultrasonography, and rectal palpation techniques. The study involved twelve multiparous, non-lactating one-humped She-camels.The sensitivity of plasma progesterone for diagnosing pregnant She-camels decreased (P ≤ 0.01) from 100% at day 20 post-mating (PM) to 80% during subsequent periods. Conversely, the specificity for diagnosing non-pregnant She-camels increased (P ≤ 0.01) from 71.4% at day 20 PM to 85.7% at day 30 PM, reaching 100% at days 40, 50, and 60 PM. The sensitivity for diagnosing pregnant she-camels using ultrasonography was 100% on day 20 post-mating (PM) and 80% during subsequent periods. The specificity for diagnosing non-pregnant she-camels increased significantly (P ≤ 0.01), rising from 71.4% on day 20 PM to 85.7% on day 30 PM and reaching 100% by days 40, 50, and 60 PM. The sensitivity and specificity of rectal palpation achieved 100% on days 60 and 90 PM. In conclusion, we can effectively detect early and accurate pregnancy in Iraqi she-camels using progesterone levels and ultrasonography techniques as early as day 20 PM.